Apatinib treatment efficiently delays biochemical-only recurrent ovarian cancer progression - Zhongyu Wang; Yake Huang; Ling Long; Li Zhou; Yan Huang; Lei Gan; Aimin Pu; Sufen Li; Rongkai Xie (BMC, 2021)
Abstract Background Biochemical recurrence is defined as only rising CA-125 but no radiographic evidence of disease; noteworthily, it generally precedes the onset of clinical evidence. Now treatment strategies of biochemical recurrence ovarian cancer (OC) remain controversial. Apatinib as monotherapy or in combination with other chemotherapeutic agents has shown its effect in the treatment of some advanced malignancies. In our study, we focused on the efficacy of apatinib in recurrent OC, especially its clinical activity in biochemical-only recurrent OC patients. Methods We retrospectively analyzed clinical material of 41 recurrent patients who had received apatinib monotherapy or apatinib plus chemotherapy between June 2016 and August 2018. Apatinib was administered at a 500mg daily dose. Response was determined according to measurable disease or serum carbohydrate antigen (CA)-125 levels. Progression-free survival (PFS) was estimated by Kaplan-Meier method. Results All patients were evaluable, 19 (46.34%) had biochemical relapse and 22 (53.66%) had clinical relapse. The objective response rate (ORR) and disease control rate (DCR) in the overall population were 31.71% and 78.05%, respectively. The median PFS was 7 months (95% confidence interval 5.43-8.57). And in patients with biochemical-only relapse, the median PFS was 6 months, with ORR of 26.32% and DCR of 89.47%. Conclusions Apatinib is a well-tolerated and effective agent to delay clinical progression of patients with biochemical-only recurrent OC. More important, our study shows the promising prospect for treating OC patients with asymptomatic biochemical relapse.